Knowledge, attitude, practice about awareness of basic life support facilities for medical emergencies among dental practitioners: a cross sectional questionnaire study - Fegade, Anushree Ashish; Pereira, Treville; Anjali, A. K.; Lalai, Megha; Pereira, Christina; Kallianpur, Ruchika (International Journal Of Community Medicine And Public Health, 2023)
Background: Healthcare professionals should be trained in basic life support (BLS), as it is a basic skill which can save lives if implemented timely. An ability to react immediately to the emergency at hand and having the proper equipment and drugs needed for the emergency, can mean the difference between successful management and failure. Objective of this study is to assess the knowledge, awareness and attitude of dental practitioners towards BLS facilities. Methods: This is a cross sectional study conducted from January to March 2021 among 250 dental interns, BDS and MDS doctors by assessing responses to 10 selected questions pertaining to BLS among dental practitioners in Mumbai/Navi Mumbai. Inclusion criteria: BDS, MDS doctors. Results: The results of my study showed that almost (77.5%) enquire about medical history. Only (32.2%) felt competent in responding to emergency situation at clinics. (46.6%) were confident about administrating IV, I.M injections and performing cardiopulmonary resuscitation (CPR). They were also assessed for the emergency drugs and emergency kits, which were available with (49.5%). Conclusions: The survey shows that there is substantial lack of BLS knowledge among dental practitioners. Prompt recognition & efficient management of medical emergencies can increase the likelihood of a satisfactory income. This is feasible by incorporating BLS in academic curriculum on regular basis and through hands on workshops.